Knowledge and Practice of Valuation Methods by Real Estate Practitioners - Armones, Carlos L.; Caelian, Merlita V.; Jubelag Jr. VIII, Francisco G. (Philippine Social Science Journal, 2022)
Property valuation services provided by real estate practitioners significantly impact global economies because property valuation methods affect the accuracy of the estimates of the market value of real properties. The paper assessed the level of knowledge and extent of practice of real estate practitioners on the valuation methods. Likewise, the study investigated the challenges encountered by respondents in their practice. This descriptive-comparative and correlational study utilized a test questionnaire to measure the level of knowledge and a researcher-made survey instrument to measure the extent of practice on the 98 licensed real estate practitioners. With descriptive and inferential analyses, the findings ascertained respondents’ average level of knowledge on both methods of valuation. While for the extent of practice of valuation methods, findings revealed great extent for traditional method while moderate for advanced method. Consequently, significant differences were found when the length of practice of the profession, designation, and educational attainment were used as variables. Results disclosed an inverse relationship between knowledge and practice. The major challenge encountered by real estate practitioners is the influence of property owners in fixing the value of real properties, which hinders a fair, accurate, and ethical valuation.